2005
DOI: 10.1021/bi047318e
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Crystal Structure of Manganese Peroxidase:  Substrate and Inhibitor Complexes,

Abstract: Manganese peroxidase (MnP) is an extracellular heme enzyme that catalyzes the peroxidedependent oxidation of Mn II to Mn III . The Mn III is released from the enzyme in complex with oxalate. One heme propionate and the side chains of Glu35, Glu39, and Asp179 were identified as Mn II ligands in the 2.0 Å resolution crystal structure. The new 1.45 Å crystal structure of MnP complexed with Mn II provides a more accurate view of the Mn-binding site. New features include possible partial protonation of Glu39 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 47 publications
5
56
0
Order By: Relevance
“…The Mn(II) is located in a cation-binding site at the surface of the protein and coordinates to the carboxylate oxygens of Glu35, Glu39, and Asp179, the heme propionate oxygen, and two water oxygens. The site has considerable flexibility to accommodate the binding of a wide variety of metal ions [119,120]. Two heptacoordinate structural calcium ions, one tightly bound on the proximal side and the other bound on the distal side of the heme, are important for thermal stabilization of the active site of the enzyme [119].…”
Section: Molecular Structurementioning
confidence: 99%
“…The Mn(II) is located in a cation-binding site at the surface of the protein and coordinates to the carboxylate oxygens of Glu35, Glu39, and Asp179, the heme propionate oxygen, and two water oxygens. The site has considerable flexibility to accommodate the binding of a wide variety of metal ions [119,120]. Two heptacoordinate structural calcium ions, one tightly bound on the proximal side and the other bound on the distal side of the heme, are important for thermal stabilization of the active site of the enzyme [119].…”
Section: Molecular Structurementioning
confidence: 99%
“…Mn 2+ performs the role of mediator for MnP. High resolution crystal structure has revealed that MnP catalyzes the peroxide dependent oxidation of Mn 2+ to Mn 3+ and Mn 3+ is released from the enzyme in complex with oxalate or with other chelators (Sundramoorthy et al 2005). Along with pyrophosphate, the various Mn 2+ chelators that enhance the activity are malonate, oxalate, L-tartrate, oxaloacetate, Lmalate, and methylmalonate (Mäkelä et al 2005).…”
Section: Enzyme System Of White Rot Fungimentioning
confidence: 99%
“…(1a) (1b) Other examples of such mononuclear redox-active enzymes include the manganese peroxidase responsible for lignin degradation by white-rot fungus [10][11][12]; a unique Mndependent form of lipoxygenase [13][14][15][16]; oxalate decarboxylase [17,18]; as well as an extradiol catechol dioxygenase [19][20][21]. …”
Section: Mn-containing Biological Systemsmentioning
confidence: 99%
“…Many Mn-dependent enzymes take advantage o f the rich redox chemistry available to the metal, accessing the +2, +3, +4, and perhaps even the +5 oxidation states during their turnover. For example, Mn-superoxide dismutase (MnSOD), which detoxifies the cell of the superoxide radical , cycles between the Mn(II) and Mn(III) oxidation states via the ping-pong type mechanism shown below [5][6][7][8][9].(1a) (1b) Other examples of such mononuclear redox-active enzymes include the manganese peroxidase responsible for lignin degradation by white-rot fungus [10][11][12]; a unique Mndependent form of lipoxygenase [13][14][15][16]; oxalate decarboxylase [17,18]; as well as an extradiol catechol dioxygenase [19][20][21]. …”
mentioning
confidence: 99%